Breves considerações sobre o papel de Pierre Monbeig na formação do pensamento geomorfológico uspiano - Antonio Carlos Vitte (Confins)
This paper argues that the geomorphological uspian thought was developed from the ideas of Pierre Monbeig. In this process, the notion of geographical complex, defined as a relationship between culture and nature through the material history of society, made it possible to understand relief as the necessary architecture for the development of territorial history of a region. The direct influence of this postulate is the work of Aziz Nacib Ab'Saber, where he organizes the uspian geographical geomorphology and which mark the brazilian interpretation of the relief in terms of analytical resources, epistemic, and methodological.